Design and Development of a Web and Mobile-Based Project Management System for Software Enterprises - Mushyafa Ali; Adam Sekti Aji (bit-Tech, 2026)
CV Webpakar, a technology company specializing in software development services, faces significant challenges in internal project management due to its reliance on un-integrated communication tools, leading to miscommunication, undocumented task assignments, and project delays. This study aims to design, develop, and evaluate an integrated project management system utilizing web and mobile platforms, grounded in the DeLone and McLean Information Systems (IS) Success Model as the theoretical lens for assessing system quality and user satisfaction. The system was developed using an Agile methodology with a client-server architecture: a Next.js web application for administrators, a React Native mobile application for team members, and a Django REST Framework backend connected to a MySQL database via RESTful APIs. System evaluation was conducted through a multi-dimensional approach encompassing functional testing (32 test cases, 100% pass rate), API performance benchmarking (average response time of 155.6 ms across 14 endpoints, all below the 300 ms threshold), and usability evaluation using the System Usability Scale (SUS), which yielded an average score of 78.5, falling within the "Good" and "Acceptable" categories. The results demonstrate that the system effectively addresses the operational inefficiencies of manual project management, while providing empirical evidence that high system quality and usability contribute to positive net benefits in SME contexts, consistent with the D&M IS Success Model. This study contributes to the information systems body of knowledge by providing a validated dual-platform project management implementation with quantitative evaluation evidence, an area underexplored in prior literature. Future work includes enhancing dashboard analytics and conducting longitudinal user adoption studies.